Impacts of the land use transition on ecosystem services in the Dongting Lake area - Xuan, Shi; Qimeng, Ning; Zhigang, Lei (Frontiers in Environmental Science, 2024)
Urbanization-induced land use transition results in a decline in ecosystem services, which has implications for regional ecological security. In order to explore the relationship between ecosystem services and land use transition, this paper utilizes the InVEST model, geographically weighted regression model to examine the impact of land use transition on ecosystem services in the Dongting Lake area (DLA). The results showed that (1) With the change of urbanisation development, the average values of